DETERMINATION OF CLOSENESS OF ENAMEL, AS CRITERION OF ORIGIN OF ENHANCEABLE EFFACIENCE OF TEETH - Tkachenko, I.M. (World of Medicine and Biology, 2012)
In-process questions come into question about the etiologic factors of development of enhanceable effacience of teeth. Enough large interest presents research of closeness of enamel which, in our way can opinion depend on the closeness of piling of enamel prisms on unit of area. All these changes, possibly, can arise up on stadies of embruogenesis: initially is violation of structure of proteins, second time is violation of orientation and piling of crystals.